Interventional radiology placement of totally implantable venous access devices in oncology practice - Shao Jin Ong; Gopinathan Anil (Annals, Academy of Medicine, Singapore)
In November 1929, Werner Forssmann, a German surgical resident, attempted the first documented central venous catheter with a 35 cm-long catheter via his left antecubital vein.1 Although revolutionary for his time, this innovation encountered significant opposition, and he was expelled from his training programme for this unauthorised experimentation. Despite the initial censure, his idea garnered interest across the Atlantic in the US, where Andre Counard and Dickinson Richards, in the 1940s, refined his technique and used it for cardiovascular research. In 1956, Forsmann, Counard and Richards were awarded the Nobel Prize in Physiology for their work on central venous access.2 Since then, a wide variety of central venous access options have emerged. However, totally implanted venous access device (TIVAD) is unique in that it has no exposed catheter parts. This reduces the risk of catheter-related infection, increases the longevity of the access and makes it low maintenance.3 Infuse-A-Port was the first described TIVAD, reported by Niederhuber et al.2 in 1982. Since then, they have been colloquially called “ports” among other names such as port-a-cath and chemoport. Among the scientifically appropriate descriptors, TIVAD, subcutaneous venous access device (SVAD) and totally implanted venous access port (TIVAP) are frequently used in medical literature. These devices have a reservoir or chamber implanted subcutaneously. A catheter connected to this reservoir is pulled through a subcutaneous tunnel and inserted into a large vein, with its tip usually placed in a central vein. The reservoir has a self-sealing silicone diaphragm that is punctured percutaneously with a non-coring needle to gain venous access. Traditionally, TIVADs were inserted by surgeons in operating theatres; however, with the transition to imaging-guided insertion, these devices are now implanted by interventional radiologists in most high-volume centres. Interventional radiology (IR) guided placement of TIVADs has been reported to be cheaper, faster and safer with higher placement success and more accurate positioning.4